2019
DOI: 10.1038/s41385-019-0150-8
|View full text |Cite
|
Sign up to set email alerts
|

TNFα promotes mucosal wound repair through enhanced platelet activating factor receptor signaling in the epithelium

Abstract: Pathobiology of several chronic inflammatory disorders including ulcerative colitis and Crohn’s disease is related to intermittent, spontaneous injury/ulceration of mucosal surfaces. Disease morbidity has been associated with pathologic release of the pro-inflammatory cytokine Tumor Necrosis Factor alpha (TNFα). In this report, we show that TNFα promotes intestinal mucosal repair through upregulation of the GPCR Platelet Activating Factor Receptor (PAFR) in the intestinal epithelium. Platelet Activating Factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 48 publications
4
28
0
1
Order By: Relevance
“…Active and coordinated repair responses that promote epithelial cell migration and proliferation are necessary to reestablish mucosal barrier function and intestinal homeostasis (14). We and others have shown that regulated spatiotemporal recruitment of leukocytes that interact with the repairing epithelium plays an important role in ensuring timely mucosal repair (15)(16)(17). SPMs have been demonstrated to have important roles in orchestrating resolution of inflammation in different tissues by triggering anti-inflammatory and proresolution responses in immune cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…Active and coordinated repair responses that promote epithelial cell migration and proliferation are necessary to reestablish mucosal barrier function and intestinal homeostasis (14). We and others have shown that regulated spatiotemporal recruitment of leukocytes that interact with the repairing epithelium plays an important role in ensuring timely mucosal repair (15)(16)(17). SPMs have been demonstrated to have important roles in orchestrating resolution of inflammation in different tissues by triggering anti-inflammatory and proresolution responses in immune cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…PAF mediates a wide variety of cellular functions and cell–cell interactions. Therefore, PAF is involved in several physiological processes including apoptosis, physiological inflammation, wound healing, reproduction, angiogenesis, long-term potentiation, and potentially retrograde signalling [4,5,6,7]. However, PAF is also a potent pro-inflammatory mediator that is implicated in a variety of conditions and chronic diseases such as cancer, renal diseases, cerebrovascular and central nervous system disorders, allergies, asthma, infections, and cardiovascular diseases (CVD) [5,8,9,10,11,12,13].…”
Section: Platelet-activating Factormentioning
confidence: 99%
“…In addition, while traditionally considered a proinflammatory cytokine, recent evidence demonstrated that TNF-α promotes mucosal wound repair in mice by activating Wnt/β-catenin signaling, increasing epithelial cell proliferation, and upregulating expression of receptors that promote intestinal healing ( Figure 1 and refs. 32,33).…”
Section: Epithelial Cells In Cutaneous and Intestinal Wound Repairmentioning
confidence: 99%